A Taxonomy for Rapidly Changing Social Media Platforms - De, Ankolika; Cotter, Kelley (AoIR Selected Papers of Internet Research, 2026)
Social media platforms (SMPs) evolve rapidly and continually, impacting their affordances, user experiences, and societal interactions. Existing research has often analyzed these changes from organizational or technological innovation perspectives or examined SMPs and their policies in isolation, rather than within broader patterns. SMPs, however, are distinct in their logics, relevance, practices, and user engagement. Thus, we propose a taxonomy of SMP change, grounded in sensitizing concepts from literature on platform and technological evolution alongside an analysis of 400 public communication documents from Meta, YouTube, X, and TikTok. Our aim is to theorize SMP evolution and critically reassess its broader implications. Our taxonomy categorizes SMP change into three interdependent dimensions: material, algorithmic, and ideological. Material changes involve modifications to platform features, interfaces, and user experiences. Algorithmic changes refer to backend modifications that are often less transparent and largely invisible, yet they significantly shape user interactions and content visibility. Ideological changes reflect shifts in governance priorities and policy frameworks, often driven by political and economic pressures. These dimensions are not mutually exclusive but intersect in ways that redefine SMP values, affordances, impacts, and potential harms. By theorising SMP change, our taxonomy highlights the embedded politics of digital platforms and their role in shaping contemporary information ecosystems as infrastructures. This hopes to provide researchers with lens and language to critically examine how platform changes influence societal structures. We also emphasise the importance of such a language to study their growing relevance, particularly as corporate-state collaborations within SMP industries expand in unprecedented ways.